Pastures of millet or sorghum forage for steers in the growth phase (Research, Society and Development, 2020)
Annual pasture species summer are used in Brazil to supply forage in in unfavorable seasons and / or to meet more demanding categories. The objective of this study was to evaluate the forage production parameters and the development of growing steers (195.0±13.40 kg, 14 ± 0.19 months), in pastures of pearl millet or forage sorghum. Treatments consisted of: Sorghum grazing (Sorghum bicolor L. Moench) and Pearl millet grazing (Pennisetum americanum Leeke). The experimental design was randomized blocks. The experimental period was 84 days, divided into three evaluation periods. Pearl millet pasture provided a greater supply of leaf blades, in relation to forage sorghum (3.64 vs. 1.98 kg DM / 100 kg body weight), but the other characteristics did not differ between forage species (P> 0.05). The evolution of weight and body structure of steers was similar between forages, as well as the animal productivity per area unit (P> 0.05). The evaluation periods significantly influenced plant and animal production (P